Earth's Toxic Nano-compartments : Metal Behavior During Natural Nano-particle Maturation - Swenson, Ellyn (My University, 2015)
The purpose of this study was to answer this question: how do nanoparticles in natural, metal rich environments behave in terms of metal content with growth into a more "crystalline" phase?
Color poster with text, images, charts, and photographs.
Keywords: Nanoparticle maturation; Metals; Nanoparticles; Posters